11.4k views
5 votes
PLSSS HELPPPP>>> Show work Solve the system y= -x+3 y=3/2x-2

1 Answer

4 votes

Answer:

(2, 1 )

Explanation:

Given the 2 equations

y = - x + 3 → (1)

y =
(3)/(2) x - 2 → (2)

Substitute y =
(3)/(2) x - 2 into (1)


(3)/(2) x - 2 = - x + 3 ( multiply through by 2 to clear the fraction

3x - 4 = - 2x + 6 ( add 2x to both sides )

5x - 4 = 6 ( add 4 to both sides )

5x = 10 ( divide both sides by 5 )

x = 2

Substitute x = 2 into either of the 2 equations and evaluate for y

Substituting into (1)

y = - 2 + 3 = 1

Solution is (2, 1 )

User Azin Nilchi
by
4.6k points